Hunting for Sustainability: Indigenous Stewardship in the Cofán Territory of Zábalo - Michael S. Esbach; Carlos Urgilés‐Verdugo; Wendy R. Townsend; Carlos Yiyoguaje (Conservation Letters, 2024)
ABSTRACT Indigenous lands are increasingly recognized for their critical role in biodiversity conservation. However, concerns persist about the sustainability of hunting practices within these territories. This study investigates the long‐term impact of Indigenous hunting practices on wildlife populations in the Cofán territory of Zábalo, Ecuador. We employed line transect surveys to estimate wildlife densities over three periods (2001–2003, 2006–2009, and 2018), focusing on 16 species that are integral to local livelihoods and subject to community management. Our results indicate generally stable or increasing populations for most species, particularly in nonhunted areas, where spatial restrictions are enforced. The Cofán's ability to sustainably manage relations between humans and wildlife is largely attributable to their adaptive management system, which includes species‐specific regulations and spatial zoning, and is realized through community decision‐making, knowledge sharing, and an ethos of care. These findings demonstrate that Indigenous stewardship can effectively sustain biodiversity in complex biocultural systems. The study underscores the importance of integrating Indigenous knowledge with scientific approaches to achieve long‐term conservation goals.